INVESTIGATING THE CAUSES OF ENGLISH ERRORS PRODUCED BY SENIOR HIGH SCHOOL STUDENTS IN BOJONEGORO - Ahmad Tauchid; Mohammad Fatoni (Journal of English Language Learning, 2019)
English especially in Indonesia is still considered a foreign language. This presumption makes English undeveloped in Indonesia. Even the students of senior high school that have obtained English subject since they are at junior high school are not able to master English properly and correctly because there are many errors they produce. In this research, two research questions are formulated as follows: (1) What kinds of errors are produced by senior high school students in Bojonegoro? (2) What factors cause the students to produce those errors? The researcher then puts some objectives as follows: (1) To find out what kinds of errors are produced by senior high school students in Bojonegoro? (2) To identify what factors cause the students to produce those errors? The research design which is used by the researcher is a quantitative approach, through a survey method. The results of this research show that from 84 respondents that are taken from 3 different senior high schools in Bojonegoro have tendency to produce English errors which are related to Morpho-Syntactic Errors as much as 71.4%. Then factors which cause a large number of errors are owing to Intralingual errors as much as 59.5%, namely because there is presumption in their mind that English is very difficult to study.